Design and Implementation of A Web-Based and or Code-Based Fire Extinguisher Management Information System: A Case Study at PT Botto Global Mandiri - Fiqhy Faradisa Al Bina; Asep Arwan Sulaeman; Sophian Andhika Sardi (Publikasi Indonesia, 2026)
PT Botto Global Mandiri is a company engaged in fire safety systems with a focus on procurement, inspection, and management of Light Fire Extinguishers (APAR). The management of customer data, fire extinguishing data, and refill data that is still done manually using paper forms causes data inaccuracies, service delays, and difficulties in tracking fire extinguishing history. This research aims to analyze the conditions of fire extinguisher data management, design and build a web-based information system with QR Code integration, and implement and evaluate the system in improving fire extinguisher documentation. The research uses an applied research approach with the Waterfall development method which includes needs analysis, system design, implementation, and testing. Data collection was carried out through observation, interviews, and literature studies. The system is built using the PHP programming language and MySQL database and includes three interintegrated user modules, namely Admin, Customer, and Technician. The results of the study show that the system successfully integrates customer data management, generates a unique QR Code for each fire extinguisher unit, scheduling inspections, filling out digital inspection forms through QR Code scanning, report verification, and reporting to management in real-time. Testing with the Black Box Testing method shows that all features are valid according to the specifications of the needs. Thus, the application of web technology and QR Codes has been proven to increase data accuracy, inspection process efficiency, and ease of tracking fire extinguishing history at PT Botto Global Mandiri.